Significantly Delayed Medium-Latency Response of the Stretch Reflex in Delayed-Onset Muscle Soreness of the Quadriceps Femoris Muscles Is Indicative of Sensory Neuronal Microdamage - Balázs Sonkodi; Ádám Hegedűs; Bence Kopper; István Berkes (Journal of Functional Morphology and Kinesiology, 2022)
Unaccustomed or strenuous eccentric exercise is known to cause delayed-onset muscle soreness. A recent hypothesis postulated that mechano-energetic microinjury of the primary afferent sensory neuron terminals in the muscle spindles, namely a transient Piezo2 channelopathy, could be the critical cause of delayed-onset muscle soreness in the form of a bi-phasic non-contact injury mechanism. This theory includes that this microlesion could delay the medium-latency response of the stretch reflex. Our aim with this study was to investigate this hypothesis. According to our knowledge, no study has examined the effect of delayed-onset muscle soreness on the medium-latency response of the stretch reflex. Our findings demonstrated that a significant delay in the medium-latency stretch reflex could be observed right after a multi-stage fitness test in the quadriceps femoris muscles of Hungarian professional handball players who consequently experienced delayed-onset muscle soreness. The long-latency stretch reflex and most likely short-latency stretch reflex were unaffected by delayed-onset muscle soreness in our study, which is in line with earlier findings. We translate these findings as indicative of proprioceptive Type Ia terminal microdamage in the muscle spindle in line with the aforementioned new acute non-contact compression axonopathy theory of delayed-onset muscles soreness.